Argentina (Journal of Parents and Teachers, 2026)
Among the countries of South America, Argentina stands out as the last to be conquered and colonized. It is one of the largest countries in Latin America in terms of size, population, and economic development. This article traces its history, from the first European to arrive in the territory, through the various attempts at colonization, to the path to independence, eventually becoming the “promised land of European emigration.”
Keywords: Argentina; colonization; independence; European emigration